Silicon and salicylic acid promote different responses in legume plants - Barros, Thais Chagas [UNESP]; Prado, Renato De Mello; Roque, Cassiano Garcia; Barzotto, Gustavo Ribeiro; Wassolowski, Carlos Roberto (Taylor & Francis Inc, 2018)
The foliar application of silicon (Si) and salicylic acid (SA) can be beneficial to plants. However, there are doubts about the interaction of Si and SA in the physiology and yield of legume crop. The objective of this study was to evaluate the effects of foliar application of Si and SA on the photosynthetic variables and yield of soybean and bean grains. The experiments were composed by four treatments: potassium silicate and stabilized sodium at a concentration of 3.6 g L-1 Si in the absence and presence of SA (210 mg L-1), only SA, and without Si or SA. The interaction of Si with foliar SA enhanced photosynthesis only in soybean; it did not affect the physiological variables of bean and did not alter the yield of the two crops. The results indicated that foliar Si application at high concentrations, independently of SA application, increased the physiological variables of the soybean without affecting the yield; however, the combined application of Si and SA had an adverse effect on the physiology and yield of bean.
Keywords: annual crops; beneficial element; exogenous hormone; plant physiology; yield